THE MATHEMATICAL MODELING OF HEART BEATS NUMERICALLY - Abdel Rahman Abdel Gadir , Abdel Radi; Hadi Haidar ِ Alamin Hind Abdel; Mohammed Elnaeem, Hassan Abdelrhman (International Journal For Research In Mathematics And Statistics, 2022)
Each normal heart beat begins with the discharge depolarization of the sinoatrial (SA) node, high up in the right atrium. This is a spontaneous event, occurring 60–100 times every minute. Depolarization of the SA node does not cause any noticeable wave on the standard ECG (although it can be seen on specialized intracardiac recordings). The first detectable wave appears when the impulse spreads from the SA node to depolarize the atria. This produces the P wave. The atria contain relatively little muscle, so the voltage generated by atrial depolarization is relatively small. From the viewpoint of most leads, the electricity appears. The aim of this study depends on collecting, describing and analyzing information using several examples and types of curves theory. Several stages of the proposed models are designed and implemented on the solution programs used in Matlab programming .The quality algorithm was programming . The quality algorithm was used and developed to classification heart beats for accurate results. The proposed model contributed to providing an integrated computer solution for all stage of the classification starting from the stage of classification of heart beats in curve theory and the stage of displaying and representing the results graphically in the Matlab program . this was done by sampled taker ECG from patients to reach accurate readings that provide an ideal model applicable in many of the techniques that contribute to solving our daily problems.